Business Failure Risk Analysis in Companies listed on the IDX 2019-2020 - Umar Hamdan Nasution; Listya Devi Junaidi (Jurnal Riset Akuntansi dan Keuangan, 2022)
In Indonesia, the COVID-19 virus has rendered about 80% of typical tasks impossible. Community restrictions have an impact on corporate activity, which in turn has an impact on the economy. Two out of every three enterprises questioned in Indonesia had temporarily or permanently halted operations, according to the International Labor Organization (ILO). The purpose of this study is to examine the risk of business failure in businesses listed on the Indonesia Stock Exchange, as well as the factors that influence that risk. The descriptive analysis, classical assumption testing, and inference analysis employing multiple regression methods were used in this study. The risk of business failure as proxied by the Z Score, current ratio (CR), and company size among firms listed on the Indonesia Stock Exchange in 2019-2020 is the data used in this study. There were 411 firms in total in this study's sample. Secondary data in the form of firm financial report data and the publication of "IDX Annual Statistics" for 2019-2020 was used in this study. The current ratio and firm size have a strong positive effect on the likelihood of business failure, either partially or simultaneously, according to the findings of this study, with a 27.6% influence level. Maintaining liquidity and firm assets is a critical strategy for business continuity in challenging circumstances like today, even if it has a minor impact.